Biosorption of lead(II) ions from aqueous solution by peanut shells: Equilibrium, thermodynamic and kinetic studies - Tasar, Seyda; Kaya, Fatih; Ozer, Ahmet (Elsevier Sci Ltd, 2014)
In this study, the biosorption of Pb(II) ions onto peanut shells from an aqueous solution was studied in a batch system as a function of temperature, pH of the solution, contact time, initial concentration of Pb(II) ions, and peanut shell concentration. It was determined that the biosorption capacity of the peanut shells decreased as the temperature was increased. Several kinetic models were used to determine the biosorption mechanism. It was determined that the biosorption system obeyed the pseudo-second-order kinetic model by taking into account the correlation coefficient value. Calculated activation energy value (E-a) was 33 kJ/mol and indicates that physical biosorption mechanisms occurred. This value indicated that physical biosorption mechanisms occurred. The linear forms of the Freundlich and Langmuir isotherms were applied to the biosorption data, and it was concluded that the Langmuir isotherm gave a better fit than the Freundlich model based on the values of the correlation coefficients (R-2). The maximum Langmuir biosorbent capacity (q(max)) was approximately 39 mg/g. The thermodynamic parameters were calculated for the process by which Pb(II) ions were removed by the peanut shells. According to these parameters, it was observed that the biosorption of Pb( II) ions by the peanut shells is exothermic and spontaneous. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Lead(II); Peanut shells; Biosorption; Thermodynamic and kinetic parameters